The Problem of Scarcity Within the Framework of Islamic Economics - Reza Febrian; Shabri Abd. Majid (International Journal Of Economics Social And Technology, 2022)
Scarcity of goods and services is seen as a major problem in the economy ummah, as in view economy capitalist. This research is intended to find out how the concept of Islam towards goods and services as well as knowing problem tree economy according to system economy Islam. Problems that are answered by a writer with use approach methodology by normative and sociological, that is research based on the Koran and using analysis of an object problem, as well as character understanding (understand) to a phenomenon or social symptom. This research is classified as library research, data collected by the quote, adapt and analyze with use analysis contents (content analysis) to various literature which has relevance with a problem which discussed, then review and conclude. The results of the study show that there are significant differences in the fundamentals of the Islamic concept of goods and services, not all goods or objects that have a form can be said to be goods in Islam and not All forms of service are services. In addition, Islam has a view that the concept of scarcity in conventional economics does not exist, because all which created in the world is destined for man. Scarcity occurs because there is a problem distribution that is uneven.